Finding the "Cullud" Angle: Evelyn Cunningham, "The Women, " and Feminism on the Pages of the Pittsburgh Courier. Issue 4 (1st October 2020) - Walck, Pamela E.; Fitzgerald, Emily
ABSTRACT: As a popular columnist for one of the largest black newspapers in the country, Evelyn Cunningham felt the palpable, unrelenting pressure of representing her race in the press. It was the inescapable lens through which she saw the world and filled her with guilt whenever she ignored it. On the surface, Cunningham was an unlikely feminist and race crusader. In her Pittsburgh Courier column "The Women, " published between in 1951 and 1955, she was more likely to tackle topics ranging from how passé bridal showers had become to the challenges of navigating a dying romance. But as this study found, upon closer inspection, her women's column reveals a mid-century writer well ahead of her time—especially when it came to embracing her feminism, sexuality, and the world around her nearly a decade before white peers ushered in the second wave of feminism.